STUDI DESKRIPTIF BURNOUT STUDY SELAMA PEMBELAJARAN ONLINE DI MADRASAH IBTIDAIYAH NEGERI 5 JEMBRANA - Ahmad Sukartawan (UIN Kiai Haji Achmad Siddiq Jember, 2022)
The most important impact of the Covid-19 pandemic on education is that it requires all students to study online or study online from home which is a new thing that students are facing now. The purpose of this study was to determine the factors that students experience burnout during online learning at Madrasah Ibtidaiyah Negeri 5 Jembarana. The method used in this research is descriptive qualitative. Data collection tool with observation, interviews, and documentation. Based on the results of the study, the factors that affect students experiencing burnout study at Madrasah Ibtidaiyah Negeri 5 Jembarana are because: (1) difficulty in understanding the material, (2) the number of assignments given by the teacher, (3) there are no study partners during distance learning, (4) reduced concentration in learning, and (5) distance learning constraints.